Prospects for Harmonizing Regulatory Science Programs in Europe, Japan, and the United States to Advance Regenerative Medicine. (November 2016) - Milne, Christopher-Paul; Mittra, James; Kojima, Naoko; Sugiyama, Daisuke; Awatin, Josephine; Simmons, Gabrielle
Background: Regenerative medicine (RM) is a game-changing technology with the potential to repair damaged tissues and organs, but its introduction into the clinic is complicated by the fact that Europe, Japan, and the United States are struggling to make appropriate regulatory decisions about advanced technologies that are highly promising but also uncertain and potentially risky. They have adopted the new approach of regulatory science (RS), applying science-based approaches and standards to support regulatory decision making, to address the challenge. Methods: Is RS the right approach for harmonizing the regulatory mechanisms needed to integrate RM into the mainstream of the development continuum for medical products? If so, what are the prospects for harmonization? We examine the current state of the art for RM and RS in the 3 major drug development regions to answer these questions. Results: Among the practical obstacles to harmonization is the fact that the 3 regions represent different legal jurisdictions and health care systems, with disparate regulatory and reimbursement requirements. However, the regulatory regimes are not without commonalities. Thus, it is not the practical differences that should be debated but rather how best to enhance collaboration. Conclusions: Just as consistent and predictable regulatory support founded on common principles in regulatory science provide the confidence and certainty required to bolster investment in regenerative medicine, harmonization is essential to building that framework on a global scale.